Development of Large Format NMC-Graphite Lithium Ion Pouch Cell with Aqueous Processed Electrodes. (30th August 2016) - Kvasha, Andriy; Urdampilleta, Idoia; De Meatza, Iratxe; Colombo, Roberta; Ulmann, Pirmin; Gulas, Michal; Gutierrez, Cesar; Bengoechea, Miguel; Blazquez, Jose Alberto; Miguel, Oscar; Grande, Hans-Jurgen
Abstract : The development of a large format LiNi0.33 Mn0.33 Co0.33 O2 (NMC) - Graphite pouch cell with both electrodes prepared using waterborne PVdF binders is reported. The formulations and design of the positive and negative electrodes have been optimized to meet the MAT4BAT EU project objectives. The negative and positive electrode slurries with elaborated formulations have been scaled up effectively to kilogram scale and 100 meters length double-side coated electrodes have been manufactured. Finally, an NMC-Graphite pouch cell with nominal capacity 17 Ah demonstrated promising C-rate capability and long term cyclability reaching 80% of initial discharge capacity after 3, 200 cycles with 100% depth of discharge.